One-pot synthesis of long-chain monodisperse π-conjugated oligomers terminated by C–H or C–Br bonds. (January 2020) - Zhang, Xiao-Feng; Cheng, Jing-Zhao; Liu, Hui; Shan, Qian; Jia, Gui-Xiao; Wen, He-Rui; Liu, Shi-Yong
Abstract: Two series of twelve D-A oligomers oligo (DPP- co -fluorene) chain-terminated respectively by C–H and C–Br bonds have been readily synthesized via two single pots of direct C–H arylation between thienyl-flanked diketopyrrolopyrrole (DPP) and 2, 7-dibromo-9, 9-dihexylfluorene (DBFL) in non-equimolar ratios of 1.5:1 and 1:1.5. The correlation between the yields of oligomers and monomers feed ratios has been revealed. The oligomerO ′7, which consists of 8 fluorene and 7 DPP units, is the longest monodisperse D-A conjugated oligomer reported ever. The parent polymer of two series oligomers was also synthesized in parallel via equimolar polycondensation between DPP to DBFL. The structure-property relationships change with the evolution from these twelve oligomers to their parent polymer have been studied in detail by UV–vis, cyclic voltammetry, and DFT calculation. The facile and versatile synthetic strategy here developed will open a new direction to the rapid and atom-economic synthesis of long-chain D-A π-conjugated oligomeric materials. Graphical abstract: Image 1 Highlights: Two single steps produced twelve D-A monodisperse conjugated oligomers. For the first time, halogen Br atom is introduced into D-A long-chain conjugated oligomers. OligomerO ′7 involving 8 fluorene and 7 DPP units is the longest D-A conjugated oligomers reported ever. The correlation between the yields of conjugated oligomers and the monomer feed ratios has been revealed.